Pengaruh kualitas pelayanan dan efektivitas sistem perpajakan elektronik terhadap kepuasan wajib pajak di kantor pelayanan pajak - Tiarma; Ery Bestary Al Haitamy; Ferdyan Wana Saputra (LP2M Politeknik Jambi, 2025)
This study aims to analyze the relationship between service quality, the effectiveness of the electronic tax payment system, and taxpayer satisfaction at the Pratama Tax Office in Jambi Pelayangan. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 taxpayers residing in the Alam Barajo District, Jambi. Data analysis was conducted descriptively and associatively using SPSS software version 30.0. The results show that service quality and the electronic tax system have a positive and significant impact on taxpayer satisfaction. These findings indicate that improving service quality and optimizing a technology-based tax payment system can enhance taxpayer satisfaction and compliance. The implications of this study highlight the importance of innovation in tax services, particularly in implementing a more efficient digital system. By increasing accessibility and ease of the tax payment process, tax compliance levels are expected to improve. This study contributes to policymakers in designing strategies to enhance tax services.